2022
DOI: 10.21203/rs.3.rs-1761690/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lineage-specific protein repeat expansions and contractions reveal malleable regions of immune genes

Abstract: Functional diversification, a higher evolutionary rate, and intense positive selection help a limited number of immune genes interact with many continuously evolving pathogens. Repeats in protein-coding regions are a well-known source of rapid functional diversification, adaptive variation, and evolutionary novelty. Repeats play a crucial role in biochemical functions like functional diversification of transcription regulation, protein kinases, cell adhesion, signaling pathways, morphogenesis, DNA repair, reco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The comparison of the GC content revealed that LCR-containing genes have a significantly higher %GC than genes without LCRs across the whole Tetrapoda clade (Wilcoxon test; p < 0.05). The result is consistent with previously published studies on specific gene sets (Albà and Guigó 2004;Teekas et al 2022). A high %GC in LCR-containing genes suggests that GC-rich regions are prone to LCR formation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The comparison of the GC content revealed that LCR-containing genes have a significantly higher %GC than genes without LCRs across the whole Tetrapoda clade (Wilcoxon test; p < 0.05). The result is consistent with previously published studies on specific gene sets (Albà and Guigó 2004;Teekas et al 2022). A high %GC in LCR-containing genes suggests that GC-rich regions are prone to LCR formation.…”
Section: Discussionsupporting
confidence: 93%
“…Studies highlighting the major pathways and processes of protein LCRs are scarce and are limited to specific genes (Andrade et al 2001;Deryusheva et al 2021;Teekas et al 2022).…”
Section: Lcrs Participate In a Variety Of Biological Processesmentioning
confidence: 99%
See 2 more Smart Citations